2008
DOI: 10.1007/s10311-008-0164-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PCB levels in snow from the Aconcagua Mountain (Southern Andes) using the stir bar sorptive extraction

Abstract: This paper presents a first result of an investigation of the presence of anthropogenic pollutants named polychlorinated biphenyls (PCBs, sum of 25 congeners) in snow samples in the Aconcagua Mountains in the Andean Range, along an altitudinal gradient. Samples were taken during an expedition in 2003 and analysed by using a specific technique of thermodesorption and GC-MS adapted to small amount of sample. Mountain ecosystems could be efficient natural trap of persistent organic pollutants (POPs) transported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, the analysis of PCBs in glacier ice is challenging because of the ultratrace concentrations and the demanding sample preparation, prone to contamination and/or losses. Therefore, only a few data sets of PCB concentrations in annual snow accumulation have been published. To our knowledge, there is only one ice record from a mountain glacier documenting the entire time period of industrial use of PCBs, and this record is from Svalbard in the Arctic …”
Section: Introductionmentioning
confidence: 99%
“…However, the analysis of PCBs in glacier ice is challenging because of the ultratrace concentrations and the demanding sample preparation, prone to contamination and/or losses. Therefore, only a few data sets of PCB concentrations in annual snow accumulation have been published. To our knowledge, there is only one ice record from a mountain glacier documenting the entire time period of industrial use of PCBs, and this record is from Svalbard in the Arctic …”
Section: Introductionmentioning
confidence: 99%
“…Studies, such as that of Quiroz et al (2009), have shown the presence of anthropogenic pollution in the Aconcagua valley, which is located very close to the main highway that links Chile and Argentina, with very large flow of trucks, buses and cars, throughout the year. During winter, it is visually evident that black carbon and dust particles associated with traffic deposit over the snow in the ski resort of Portillo, on the Chilean side.…”
Section: Discussionmentioning
confidence: 99%
“…Quiroz et al (2009) analyzed snow samples from the mountains of Aconcagua in the Southern Andes in January 2003 to determine PCBs. Sampling was carried out at 3,500, 4,300, 5,000, 5,800, and 6,200 m above sea level.…”
Section: Mountain Ecosystemsmentioning
confidence: 99%